Exploring the associations between early maladaptive schemas and impulsive and compulsive buying tendencies - Rocha, Susana; Fernández, Xosé Manuel; Castro, Yolanda Rodríguez; Ferreira, Simão; Teixeira, Liliana; Campos, Carlos; Rocha, Nuno Barbosa (Frontiers in Psychiatry, 2023)
The main purpose of this preliminary study was to investigate a potential relationship between early maladaptive schemas (EMSs) and impulsive and compulsive buying tendencies in a sample of young adults (college students). This research adds to the cognitive perspective of consumer behavior that the cognitive schemas putatively associated with early experiences may have a strong impact on impulsive and compulsive buying. Data was obtained from 365 participants in a cross-sectional study design. Participants completed an online survey with the following instruments: Young Schema Questionnaire; Impulsive Buying Tendency Measurement Scale; Richmond Compulsive Buying Scale; and Hospital Anxiety and Depression Scale. Using multiple linear hierarchical regressions, we confirmed that the domain of over vigilance and inhibition schemas was positively associated with impulsive and compulsive buying tendency and the domain of impaired limits was inversely associated. Being a female was also a predictor of impulsive buying and compulsive buying. The results were discussed in terms of the coping mechanisms to deal with negative emotions, as a way to obtaining rewards, or as a way to escape painful self-awareness. Other mechanisms were also explored related to the internalization of perfectionist expectations and the propensity to shame.